O conflito autonomia-dependência na adolescência e a questão das drogas: intervenção em um grupo de adolescentes do CRAS - Vizzuso, Patrizia [UNIFESP] (2014)
This study evaluated the effects of an intervention on a group of teenagers attending CRAS in the city of Guarujá, specifically in PROJOVEM Adolescent Program, to promote health. Using action-research as a method, reflexion groups as a tool, and psychoanalysis as a theoretical framework, this research investigated the effects of intervention in relation to dependency-autonomy conflict in this group with the purpose of their awareness taking by adolescents, particularly with the issue of drug use. Proposing a more horizontal relationship in the group, it could be seen that the reference of social relationship that teenagers had was vertical, which favored the dependency of these young people, making them more vulnerable. During the process there were changes in the position of the participants in relation to autonomy, reaching a group production making. It was concluded by noting benefits of a reflection space for teens that operates analogously to a potential space in winnicottians terms, encouraging a greater awareness and more creative responses to their conflicts, and consequently, greater autonomy.